Using sewage sludge as a flue gas denitration agent for the cement industry: Factor assessment and feasibility. (1st July 2019) - Fang, Ping; Tang, Zijun; Xiao, Xiang; Huang, Jianhang; Chen, Xiongbo; Zhong, Peiyi; Tang, Zhixiong; Cen, Chaoping
Abstract: In this study, the feasibility of using sludge as a flue gas denitration agent for the cement industry was evaluated, and factors affecting NOX (NO + NO2 ) removal were systematically investigated using a custom-built laboratory-scale fluid-bed reactor. The results indicate that sludge is an effective NOX reducing agent, and sludge dosage, combustion temperature, and O2 concentration greatly affect NOX removal. Finally, the optimal operation conditions for the sludge denitration process were determined. With a sludge dosage of 0.75 g/min, sludge particle size of 60–80 mesh, combustion temperature of 900 °C, gas flow rate of 18 L/min, O2 concentration of 3% (v/v), and the CO2 concentration of 25% (v/v), the maximum NOX removal efficiency could reach 74.16 ± 4.65%. Moreover, preliminary research on the mechanism showed the occurrence of homogeneous and heterogeneous NOX reductions during the sludge denitration process. The homogeneous NOX reduction considerably contributes to NOX removal. Therefore, the use of sewage sludge as a flue gas denitration agent for the cement industry is feasible. Graphical abstract: Image 1039245 Highlights: Using sludge as a flue gas denitration agent for cement industry is feasible. Factors affecting sludge denitration performance were carefully studied. The homogeneous NOx reduction has a major contribution to NOx removal. It is also a cost-effective and sustainable sludge-disposal method.